The pedagogical eclipse: A critical approach to postmodern education from the systemic realist thinking of Xavier Zubiri - Huaytan Jaramillo, Afranio U. (2024)
Educational models have experienced drastic changes in the first decades of the 21st century, influenced by the emergence of new technologies such as ICT and AI. These changes are rooted in the philosophical and anthropological assumptions of postmodernity, marked by the relativization of truth and the emergence of a media society. The research aims to critically analyze contemporary and postmodern education from the perspective of Xavier Zubiri, a Spanish philosopher. Zubiri advocates an approach that recognizes reality as an objective and transcendent entity, leading to a concept of truth based on consistency between reality and human knowledge. This perspective allows us to rethink education as a process that seeks the holistic development of the person, in line with the Greek tradition of paideia. Philosophical hermeneutics is applied as a methodology, focusing on contextualized understanding, dialogue, the horizon of meaning, critical interpretation and educational ethics, with the aim of improving the quality and relevance of education.